Pengaruh Citra Merek, Kepercayaan Konsumen, dan Persepsi Risiko terhadap Loyalitas Konsumen AMDK Aqua : The Influence of Brand Image, Consumer Trust, and Risk Perception on Aqua Bottled Water Consumer Loyalty - Ersanda Aprilia; Asep Dony Suhendra (CV Warnak Johanna Nusantara, 2026)
The increasingly competitive bottled drinking water industry in Indonesia has encouraged companies to better understand the factors influencing consumer loyalty. This study aims to examine the effects of brand image, consumer trust, and perceived risk on consumer loyalty toward Aqua bottled drinking water in Cengkareng District, West Jakarta. A quantitative approach was employed using multiple linear regression analysis with IBM SPSS. Data were collected through questionnaires distributed to 100 respondents selected using purposive sampling. The results indicate that consumer trust has a positive and significant effect on consumer loyalty, whereas brand image and perceived risk do not have a significant effect. Simultaneously, brand image, consumer trust, and perceived risk significantly influence consumer loyalty. The coefficient of determination (R²) of 0.713 indicates that the independent variables explain 71.3% of the variation in consumer loyalty, while the remaining 28.7% is explained by other factors outside the research model.